2016
DOI: 10.1093/eep/dvw018
|View full text |Cite|
|
Sign up to set email alerts
|

Adolescent epigenetic profiles and environmental exposures from early life through peri-adolescence

Abstract: Epigenetic perturbations induced by environmental exposures at susceptible lifestages contribute to disease development. Even so, the influence of early life and ongoing exposures on the adolescent epigenome is rarely examined. We examined the association of exposure biomarkers for lead (Pb), bisphenol A (BPA), and nine phthalates metabolites with blood leukocyte DNA methylation at LINE-1 repetitive elements and environmentally responsive genes ( IGF2 , H19 , and HSD11B2 ) in peri-adolescents. Participants ( n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 70 publications
2
55
1
Order By: Relevance
“…Goodrich et al evaluated prenatal exposure to BPA and its association with DNA methylation in peri-adolescence [58]. Maternal BPA ( in utero ) exposure was measured in 3 rd trimester (T3) urine samples, and peri-adolescence exposure was measured in participants between the ages of 7–14.…”
Section: Prenatal Exposure To Pb and Bpa In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…Goodrich et al evaluated prenatal exposure to BPA and its association with DNA methylation in peri-adolescence [58]. Maternal BPA ( in utero ) exposure was measured in 3 rd trimester (T3) urine samples, and peri-adolescence exposure was measured in participants between the ages of 7–14.…”
Section: Prenatal Exposure To Pb and Bpa In Humansmentioning
confidence: 99%
“…Maternal Pb exposure was evaluated using three biospecimens, and childhood Pb exposure was evaluated across three age ranges (1–4, 6–12 and 8–12) to evaluate the impact of Pb exposure on repetitive elements and environmentally responsive genes [58]. Average maternal blood Pb during pregnancy was associated with LINE-1 hypomethylation.…”
Section: Prenatal Exposure To Pb and Bpa In Humansmentioning
confidence: 99%
“…Using data from a longitudinal birth cohort, Goodrich et al (2016) reported that blood leukocyte DNA methylation in participating periadolescents was positively correlated with increasing BPA levels both in archived maternal urinary samples collected during the third trimester of pregnancy and in the urinary samples obtained from the peri-adolescents themselves. Although this positive correlation was observed at all analyzed loci, namely, the LINE-1 repetitive elements, and imprinted genes H19, IGF2, and HSD11B2, statistical significance was observed only when associating maternal urinary BPA levels with IGF2 hypermethylation (Goodrich et al 2016). However, these findings are not completely concordant with the previously described results in human subjects whereby BPA exposure was associated with decreased LINE-1 methylation.…”
Section: Bisphenol A-a Stealthy Hazardmentioning
confidence: 99%
“…As the statistical tools emerge to characterize the full exposome, studies on the combined burden of multiple exposures on the epigenome can be undertaken. An early example has been a study of the independent effect of maternal lead on LINE-1 DNA methylation changes of children, wherein, Goodrich and colleagues considered and controlled for the influence of maternal bisphenol A and nine phthalate metabolites that were represented by four components created by principal components analysis [19], although the potential synergistic effects were not examined. Another recent study has demonstrated that among 16 measured chemicals, CB-105 was identified as the most “epigenetically active” pollutant for female newborns [117].…”
Section: Challenges and Outlookmentioning
confidence: 99%
“…Recent data also suggests that through epigenetic variation, the organism not only reacts to the environmental experience of the current environment during the pre-/post-natal period [19] but also, potentially, to the environmental events experienced by its parental ancestors (reviewed by [2022]). A great body of literature has made efforts to understand what epigenetic variations can be induced by what environmental factors throughout the lifetime [12,2326].…”
Section: Introductionmentioning
confidence: 99%